Optimasi Media Kultivasi Senyawa Aktif Penicillium lagena sebagai Antifungi Patogen Phellinus lamaoensis dengan Menggunakan Respon Surface Methodology - Rofiq Sunaryanto; Diana Nurani; Asep Riswoko; Siti Nabilah; Khaswar Syamsu (Seminar Nasional Lahan Suboptimal, 2018)
Sunaryanto et al, 2019. Optimization of Penicillium lagena Medium Cultivation on Antifungal Pathogen of Phellinus lamaoensis using Response Surface Methodology. pp. 410-420. Phellinus lamaoensis (Murr.) Hein is fungal pathogen that can cause brown root rot disease in cocoa, tea, rubber, and coffee plants. Endophytic fungi, Penicillium lagena, isolated from bandotan (Ageratum conyzoides Linn.), medicinal plant, is able to inhibit the growth of pathogenic, P. lamaoensis. The effect of carbon source, nitrogen source, and mineral solution was studied. Lactose, yeast extract, and mineral solution were media components which showed significant effect toward production of P. lagena active compound. Composition optimization of these three medium components was done by response surface methodology (RSM). The Optimal response region of the significant factor was predicted by using a second order polynomial model with statistical design, central composite design (CCD). Higest production of P. lagena active compound by quadratic model was predicted to be 69.233% with medium composition 44.77 g L-1 lactose, 13.02 g L-1 yeast extract, and 15.95 mL L-1 mineral solution. Verification value in laboratory is 58.365%, lower 15.7% than its prediction. Optimization increase P. lagena active compound 9 fold compared to unoptimize media.